Analisis Faktor-Faktor Peningkatan Kepuasan Pelanggan pada Restoran Sambal Bakar Indonesia Cabang Duren Sawit di Jakarta - Putri Azzahra; Joko Ariawan (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Customer Customer satisfaction is a crucial factor in maintaining customer loyalty and enhancing the competitiveness of restaurant businesses. This study aims to analyze the level of customer satisfaction, identify the factors influencing customer satisfaction, and explore customers' experiences while consuming products at Sambal Bakar Indonesia Restaurant, Duren Sawit Branch, Jakarta. The study employed an exploratory qualitative approach using observation, interviews, and documentation. The data analyzed included sales revenue, customer transaction volume, and customer complaints during the period of January 2025 to April 2026. The findings indicate that the overall level of customer satisfaction is considered good, as reflected in increased sales revenue, stable customer transaction numbers, and a low complaint rate. The factors influencing customer satisfaction include product quality, service quality, price, restaurant atmosphere, and customer experience, with product quality identified as the most dominant factor. Nevertheless, several aspects still require improvement, including service speed, dining area comfort, and queue management during peak hours. Therefore, the restaurant is recommended to maintain its product quality, improve service quality, ensure that pricing remains consistent with the quality provided, enhance the restaurant atmosphere, and create a more positive customer experience in order to increase customer satisfaction and loyalty.